The Contribution of Religion to Restorative Justice Behind Bars - Stamatakis, Nikolaos (Journal of law, religion and state, 2013)
The present article discusses restorative justice as a distinct way of looking at criminal justice, in particular at imprisonment. It aims to explain how and why some of the fundamental goals of restorative justice, such as reconciliation, reintegration, encounter, and forgiveness are more compatible with the Christian doctrine than with most present approaches to crime. Exploring the conceptual relationship and the contribution of Christianity to the promotion of restorative justice, and vice-versa, a second practical compatibility emerges between Christianity and imprisonment, with reference specifically to the restorative justice programs developed by faith-based organizations behind prison bars in New Zealand and South Africa.